Uc Esport Instagram Management - KASHOGIE, Natanael Axelino Antari; WONO, Hilda Yunita (International Journal of Environmental, Sustainability, and Social Science, 2024)
Marketing using the internet or electronic media has experienced a significant increase. The development of this technology is increasingly mushrooming because the internet makes it easier to search for information and communicate quickly and remotely. One of them is carrying out promotional activities on social media. The activity promoted on social media is UC Esports. UC Esport is one of the SMEs popular with many people because it plays MOBA games such as Mobile Legends, Valorant, PUBG, etc. UC Esport faces problems because fewer players are visiting UC Esport's Instagram to buy products and events. Therefore, researchers want to examine how UC Esport manages its Instagram account using social media theory and find out what UC Esport needs to improve in its Instagram account. This researcher used a quasi-qualitative research method. Data was collected using interview and documentation methods. The data is processed using the results of interviews, which are then transcribed, and all data is presented systematically. Then, the data will be validated using three triangulation data sources, which were collected from 3 sources in this research: managers, UC Esport followers, and UC Esport UKM leaders. After validation, researchers will conduct a reliability test. The reliability test used dependency and triangulation with experts to provide further information about this research. This research shows that UC Esport can manage an Instagram account, as evidenced by the many followers, merchandise purchases, and people participating in UC Esport activities.